Common education in schools. Gauging potentials for democratic transformation: a case study from Greece - Kioupkiolis, Alexandros (Frontiers in Education, 2023)
This article examines how educational commons, in which teaching and learning are shaped by the entire educational community on terms of equal freedom, contribute to democratic empowerment and renewal. Intervening in the critical debate over public formal education and the scope it allows for radical democratization, discussion draws on a case study conducted in the self-organized school Solidarity School Mesopotamia in Moschato, Athens, Greece. The Solidarity School is an informal tutoring or supplementary tuition school which is attached to the formal high school curriculum. One of its main objectives is to support students for the courses they attend in public schools and to prepare them for public school and university entrance exams. This attachment foists constraints on education, however, the commons-based organization and the alter-political nature of the school put a crucial twist on educational practice. This generates considerable transformative effects which are reflected markedly in the ambiance of teaching and learning. The School promotes socio-economic and political equality not only by providing free tuition to students whose families may not be able to afford private supplementary teaching and might not be able thus to enter university or to learn foreign languages. The School nourishes also a culture of equal freedom, solidarity and civic engagement which refashions the hegemonic habitus of consumerist individualism, passivity and submission to socio-political hierarchies. The article argues thus that there is room for educational commons and democratic transformation even in structures which remain tailored to formal schooling but refigure educational hierarchies and modes of governance, infusing education with an alternative democratic ethos of solidarity, equal freedom and grassroots self-organization.